Enhancing energy recovery from aquaculture residual materials: a focus on anaerobic digestion of African catfish (Clarias gariepinus) sediment sludge - Klein, Jan; Schüch, Andrea; Foth, Sebastian; Sprafke, Jan; Bischoff, Adrian; Nelles, Michael; Palm, Harry W. (Frontiers in Sustainable Food Systems, 2024)
In Germany, warm water Recirculating Aquaculture Systems (RAS) are generally integrated with biogas plants. The process sludge produced in aquaculture could be utilized to generate energy. This study investigates the potential of process sludge from commercial African catfish (Clarias gariepinus) warm water RAS, alongside associated plant production residues (whole plants and pruning residues) for energy generation through anaerobic digestion. Biogas tests, including batch, semi-Continuous Stirred Tank Reactor (CSTR), and Upflow Anaerobic Sludge Blanket Reactor (UASB) were conducted. In batch, methane yields were 229 L(N) / kg VS from the sludge and 173–184 L(N) / kg VS from the various plant substrates (cucumber, paprika, and tomato plants). During CSTR operation, mono-fermentation of sludge produced a methane yield of 265 L(N) / kg VS. Co-fermentation with 25% cucumber residues, based on VS, increased this value to 381 L(N) / kg VS. Mono-fermentation of sludge in the UASB reactor yielded a maximum of 329 L(N) /kg VS. The relatively low TS content and unfavorable C/N ratio in C. gariepinus sludge, along with the low energy density and occasional high sulfur content in the investigated plant substrates, present challenges for CSTR biogas production. These challenges can be partially mitigated through substrate combination. For mono-fermentation of African catfish RAS sludge, the UASB reactor is recommended. Improved solids separation, extraction, and concentration techniques at aquaculture operations are essential for the efficient utilization of aquaculture sludge, especially from African catfish, in biogas plants.